A prospective cohort study of pulmonary function during pregnancy in women with and without asthma. (7th February 2016) - Zairina, Elida; Abramson, Michael J.; McDonald, Christine F.; Rochford, Peter; Nolan, Gary; Stewart, Kay; Paul, Eldho; Walker, Susan P.; George, Johnson
Abstract: Background and objective : Pregnancy alters the severity of asthma unpredictably. Uncertainty still exists about longitudinal changes in pulmonary function during pregnancy in both healthy and asthmatic women. This study aimed to compare pulmonary function changes during pregnancy in healthy and asthmatic women and to determine the relationship between pulmonary function and asthma-related quality of life during pregnancy. A secondary aim was to investigate the application of forced expiratory volume in 6 s (FEV6 ) for monitoring asthma during pregnancy. M ethods : Pregnant women with ( n = 20) and without asthma ( n = 20) had pulmonary function tests at 8–20, 21–28 and 29–40 weeks gestation. Those with asthma also completed the Asthma Control Questionnaire (ACQ) and mini Asthma Quality of Life Questionnaire (mAQLQ) at each visit. R esults : Pulmonary function declined in both groups at follow-up #1 (more markedly in those with asthma) but then improved at follow-up #2 (more markedly in those with asthma). In those with asthma, ACQ scores increased, while mAQLQ scores declined at follow-up #1; whilst at follow-up #2 these changes were in the opposite direction. FEV6 and forced vital capacity (FVC) were highly correlated ( r = 0.88, p < 0.01) in asthmatics. C onclusions : Pulmonary function changes during second and third trimesters were more pronounced in asthmatics than in healthy women. FEV6 monitoring may assist pregnant women and their health professionals in optimizing asthma management. The changes in pulmonary function in women with asthma were not significantly associated with changes in asthma control or asthma-related quality of life.